Individual differences in secondary school students' conceptual knowledge : Latent profile analysis of biology concepts - Vančugovienė, Vesta (Elsevier, 2025)
Extensive research has been conducted on the misconceptions related to photosynthesis and respiration. However, most of these studies have failed to consider the heterogeneity of learners. In this study, latent profile analysis was used to determine the differences in students' understanding of biological concepts. Students' profiles were validated by relating them to their grade level, academic achievement in biology and sophistication of epistemic beliefs. Between the scientific and non-scientific understanding of photosynthesis and respiration, there were different conceptual profiles (prescientific, inaccurate preconceptions, fragmented and synthetic) in this cross-sectional study that helped in understanding the possible, qualitatively different steps between misconceptions and scientific understanding. Higher grade levels, higher biology grades and more sophisticated epistemic beliefs were related to a higher probability of belonging to the subgroups with more scientific conceptual knowledge.
Educational relevance and implications: Between the scientific and non-scientific understanding of photosynthesis and respiration, there were different conceptual profiles (prescientific, inaccurate preconceptions, fragmented and synthetic) that helped in understanding the steps from misconceptions to scientific understanding. Higher grade levels, higher biology grades and more sophisticated epistemic beliefs were related to a higher probability of belonging to the subgroups with more scientific conceptual knowledge. Teachers should be aware that a large amount of variance may present among students in terms of their level and quality of understanding of central biological topics. Accordingly, teachers should allocate time to understand the students' level and quality of prior knowledge. They should focus on helping learners integrate correct fragments of information into a full, systemic understanding as well as encourage them to critically evaluate and compare their existing conceptions with scientific explanations. To improve the understanding of science, teachers should address the topic of the nature of knowledge, taking into account key aspects of discipline-specific epistemic beliefs. This approach will help students understand the nature, foundation and principles underlying scientific research and the empirical grounds for its acceptance.